PENGEMBANGAN MATERI AJAR BERBANTUAN APLIKASI NEARPOD PADA MATERI TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VIII SMP - Muethia Arifah; Salmah Naelofaria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the development process, product format, and feasibility of the observation report (LHO) text teaching material, supported by the Nearpod application, for eighth-grade students at SMP Negeri 1 Percut Sei Tuan. The background of this study is the limited teaching material in textbooks and the lack of use of interactive learning media, which leads to low student interest and motivation in learning. The research method used is Research and Development (R&D) with the ADDIE model, limited to three stages: analysis, design, and development. Data collection techniques were carried out through interviews with teachers and the distribution of needs questionnaires to students. The resulting product is an interactive digital link containing comprehensive material ranging from definitions, structures, and linguistic characteristics of the LHO text. Validation results by material experts showed a feasibility level of 90.24%, categorized as